Bariatric surgery as an efficient treatment for non-alcoholic fatty liver disease in a prospective study with 1-year follow-up: BariScan Study - Nickel, Felix; Tapking, Christian; Benner, Laura; Sollors, Janina; Billeter, Adrian; Kenngott, Hannes Götz; Frankenberg, Moritz von; Fischer, Lars; Müller, Beat P. (Obesity surgery, 2018)
Bariatric surgery gains attention as a potential treatment for non-alcoholic fatty liver disease (NAFLD). The present study aimed to evaluate improvement of NAFLD after the two most common bariatric procedures with validated non-invasive instruments.